The interplay of blockchain technology, user-centric orientation, and cybersecurity measures in supply chains of manufacturing enterprises - Israel, Baraka (Asian Management and Business Review, 2025)
As supply chains become increasingly digitalized, cybersecurity (CBS) threats escalate, necessitating the adoption of innovative technologies such as blockchain technology (BLT) to enhance security. The purpose of this study is to examine the effect of blockchain technology (BLT) on cybersecurity (CBS) measures within the supply chains of manufacturing enterprises, considering the moderating role of user-centric orientation (UCO). The study is grounded in the Diffusion of Innovation (DOI) theory and adopts a cross-sectional quantitative research design, using a questionnaire survey to collect data from 206 supply chain partners of manufacturing enterprises in Dar es Salaam, Tanzania. Hayes’ PROCESS macro is employed to test model hypotheses. The study results exhibit a significant positive direct effect of both BLT and UCO on CBS. Furthermore, UCO positively moderates the relationship between BLT and CBS. For manufacturing enterprises and supply chain partners seeking to implement BLT to enhance CBS, the study highlights the importance of incorporating UCO into the design and implementation of security protocols, ensuring that users are educated and actively involved in CBS practices. This research contributes to the growing body of literature on BLT and CBS by exploring the under-researched moderating role of UCO. It extends the application of DOI theory to the intersection of BLT and CBS in manufacturing supply chains, offering a novel perspective on how user engagement can optimise the security benefits of emerging technologies.